Legal framework on the marine environment protection of straits used for international navigation: Has it been effective in the Straits of Malacca and Singapore? - Mohd Hazmi Mohd Rusli; Dremliuga R.; Talaat W.I. (Yijun Institute of International Law, 2024)
There are approximately 116 straits used for international navigation around the world. Some of them are important international maritime chokepoints, namely the Dover Strait, Hormuz Strait, Straits of Malacca and Singapore and the Russian straits across the Northeast Arctic Passage. Due to the high number of navigational traffic going through these straits, vessel-source pollution is endemic in these waters. This article examines the applicable international legal framework on protection of the marine environment of straits used for international navigation such as Part XII of the United Nations Convention on the Law of the Sea and other related legal measures like International Maritime Organization conventions on protection of the marine environment. This article concludes by stating that the present framework is not sufficient in properly balancing two vital interests in the maritime world - protection of the marine environment vis-à-vis shipping.